2014
DOI: 10.1111/pre.12053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiance and temperature on the photosynthesis of a cultivated red alga, Pyropia tenera (= Porphyra tenera), at the southern limit of distribution in Japan

Abstract: Summary The effect of irradiance and temperature on the photosynthesis of the red alga, Pyropia tenera, was determined for maricultured gametophytes and sporophytes collected from a region that is known as one of the southern limits of its distribution in Japan. Macroscopic gametophytes were examined using both pulse‐amplitude modulated fluorometry and/or dissolved oxygen sensors. A model of the net photosynthesis–irradiance (P‐E) relationship of the gametophytes at 12°C revealed that the net photosynthetic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 55 publications
0
29
0
4
Order By: Relevance
“…hemiphylla, although F v /F m values decreased with longer period of culture, those at 5-15°C were similar at the same other conditions (Jiang et al 2013b). Similarly, F v /F m values of P. tenera declined significantly until the temperature was over 20°C (Watanabe et al 2014). Comparably, P n is more sensitive to temperature than F v /F m (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…hemiphylla, although F v /F m values decreased with longer period of culture, those at 5-15°C were similar at the same other conditions (Jiang et al 2013b). Similarly, F v /F m values of P. tenera declined significantly until the temperature was over 20°C (Watanabe et al 2014). Comparably, P n is more sensitive to temperature than F v /F m (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Previous study on P. tenera has shown that dark respiration increased almost linearly while the gross photosynthesis decreased with temperature increasing from 6 to 34°C (Watanabe et al 2014). Whatever the reason, a decline of P n in P. katadae var.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Long and intensive selective breeding of cultivated Pyropia leads to a reduction in genetic diversity of the stock, increased fragility to adversity, and decline in product quality. Therefore, it is crucial to recruit entirely new Pyropia species (Niwa et al 2009;Watanabe et al 2014;Green and Neefus 2015;Wang et al 2016). P. dentata has been cultivated on an experimental scale in Shantou, Guangdong province over the past few years (Xu et al 2013;Chen et al 2015).…”
Section: Introductionmentioning
confidence: 99%